Evaluasi Kinerja Dinding Penahan Tanah (Retaining Wall) Pada Proyek Pembangunan Drainase Mendawai: Performance Evaluation Of Retaining Walls On The Mendawai Drainage Development Project - Saleh, Akhmad; Saputra, Norseta Ajie; Faradila, Amelia (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The issue concerning the retaining wall revolves around the potential risk of landslides triggered by soil displacement, primarily observed in the main drainage channel within Mendawai's trading district. Despite the installation of retaining walls along the channel, persistent issues have led to structural failure or even collapse. In response to this challenge, researchers aim to investigate the impact of retaining wall usage on slope stability in the construction project of drainage channels in Mendawai, Palangka Raya, Central Kalimantan. This study will utilize manual calculation methods alongside analysis using geotechnical software, specifically Plaxis 8.6. Analysis of manual calculations reveals a significant discrepancy in safety factors. Manual calculations yield a slope stability value of 1.463 and a shear stability value of 0.834, both falling below the safety standard of 1.5. Meanwhile, Plaxis 8.6 analysis indicates a retaining wall bearing capacity value of 1.599, also below the safety standard set at 3. This indicates that the retaining wall experiences failure and fails to meet the anticipated safety standards.